2013
DOI: 10.1104/pp.113.233163
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellic Acid-Induced Aleurone Layers Responding to Heat Shock or Tunicamycin Provide Insight into theN-Glycoproteome, Protein Secretion, and Endoplasmic Reticulum Stress  

Abstract: The growing relevance of plants for the production of recombinant proteins makes understanding the secretory machinery, including the identification of glycosylation sites in secreted proteins, an important goal of plant proteomics. Barley (Hordeum vulgare) aleurone layers maintained in vitro respond to gibberellic acid by secreting an array of proteins and provide a unique system for the analysis of plant protein secretion. Perturbation of protein secretion in gibberellic acid-induced aleurone layers by two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…These hydrolytic enzymes are secreted to the starchy endosperm to break down starch and protein that accumulated in the starchy endosperm to supply carbon and nitrogen used in germination. Whereas the secretion of α-amylases and cysteine proteases from the aleurone layers increased in response to gibberellic acid treatment for 24 h, the level of the barley TaPDIL-1 ortholog was not affected by gibberellic acid treatment [64], suggesting that the barley TaPDIL-1 ortholog that remains in the aleurone cell of the wheat grain may help fold the newly synthesized hydrolytic enzymes.
Figure 8 Distribution of wheat PDI family proteins in the mature aleurone cells and the protein matrix of wheat grains. Cross sections of mature grains were immunostained with sera against TaPDIL1Aα (A, F, K) , TaPDIL2 (B, G, L) , TaPDIL3A (C, H, M) , TaPDIL4D (D, I, N) , or TaPDIL5A (E, J, O) .
…”
Section: Resultsmentioning
confidence: 99%
“…These hydrolytic enzymes are secreted to the starchy endosperm to break down starch and protein that accumulated in the starchy endosperm to supply carbon and nitrogen used in germination. Whereas the secretion of α-amylases and cysteine proteases from the aleurone layers increased in response to gibberellic acid treatment for 24 h, the level of the barley TaPDIL-1 ortholog was not affected by gibberellic acid treatment [64], suggesting that the barley TaPDIL-1 ortholog that remains in the aleurone cell of the wheat grain may help fold the newly synthesized hydrolytic enzymes.
Figure 8 Distribution of wheat PDI family proteins in the mature aleurone cells and the protein matrix of wheat grains. Cross sections of mature grains were immunostained with sera against TaPDIL1Aα (A, F, K) , TaPDIL2 (B, G, L) , TaPDIL3A (C, H, M) , TaPDIL4D (D, I, N) , or TaPDIL5A (E, J, O) .
…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we could explicitly identify more than 10 Golgi-resident proteins such as cell wall synthesis-associated proteins (e.g., UDP-glucuronic acid decarboxylase, A0A287H8Z0), which are parts of the glycosylation processes (Supplemental Table 2). It is possible that these identified proteins are active in aleurone, as previous data characterized the barley aleurone N-glycoproteome, in which numerous N-glycosylation sites were identified that play key roles in protein processing and secretion 73 .…”
Section: Discussionmentioning
confidence: 92%
“…Tibbot et al [ 17 ] observed that the principal proteins in endosperm recognised by an Agl97 antiserum were of 101 and 95 kDa at 4 dpi, but of only 81 kDa two days later. Other possible modifications include variable levels of glycosylation and non-enzymic glycation, both of which have been proposed to account for the occurrence of multiple forms of other endosperm proteins [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%